The Effect of Brand Image and Design Innovation on Consumer Purchase Interest in Export Bag Products through Perceptions of Product Quality after Rebranding - Adelia Tiara Andani; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze the effect of brand image and design innovation on consumer buying interest in Exsport Bag products through the mediating variable of perceived product quality. This study focuses on Exsport Bag products following a rebranding effort, with the objective of assessing the impact of the implemented brand image and design innovations on quality perceptions and consumer appeal. It is posited that brand image has the capacity to engender favourable associations, whereas design innovation confers additional value in terms of both aesthetics and functionality, which in turn affects purchase intention. This study employs a quantitative methodology utilizing a survey approach with respondents who are familiar with the Exsport brand and the subsequent rebranding efforts. The data were analyzed using the structural equation modeling (SEM) method to test the relationship between the independent variables (brand image and design innovation), the mediating variables (perceived product quality), and the dependent variable (consumer purchase intention). The findings of this study are anticipated to inform the refinement of a more efficacious rebranding strategy for Exsport, particularly in terms of fortifying brand image and devising designs that align with consumer needs and preferences. Moreover, this research is also expected to offer novel insights for academics in comprehending consumer behavior pertaining to rebranding within Indonesia’s local fashion industry.